Responsive hetero-organelle partition conferred fluorogenic sensing of mitochondrial depolarization. Issue 3 (21st November 2016) - Xue, Zhongwei; Zhao, Hu; Liu, Jian; Han, Jiahuai; Han, Shoufa
Abstract : A hetero-organelle partition and lysosome activable sensor was developed for fluorogenic detection of mitochondrial depolarization in autophagy and cell death. Abstract : Malfunctioning organelles are often difficult to probe with classical organelle-homing sensors owing to disruption of physiological organelle-probe affinity. We herein report the use of a responsive hetero-organelle partition and signal activable probe (RC-TPP) for detecting mitochondrial depolarization, a pathologically relevant event featuring loss of the electrical potentials across the mitochondrial membrane (Δ Ψ m ). Partitioned in mitochondria to give blue fluorescence, RC-TPP relocates into lysosomes upon mitochondrial depolarization and exhibits red fluorescence triggered by lysosomal acidity, enabling determination of autophagy relevant mitochondrial depolarization and the chronological sequence of mitochondrial depolarization and lysosomal neutralization in distinct cell death signalling pathways. As an alternative to classic homo-organelle specific molecular systems, this hetero-organelle responsive approach provides a new perspective from which to study dysfunctional organelles.